Recent Advances in the Use of Metal-Organic Frameworks for Dye Adsorption - Au, Vonika Ka-Man (Frontiers in Chemistry, 2020)
Organic dyes are heavily used in industries for the manufacture of colored goods. This has eventually resulted in the generation of contaminated wastewater which is hard to be purified. Recent studies have demonstrated that metal-organic frameworks (MOFs), a class of supramolecular materials of immense interest, are useful in the adsorption of organic dye molecules because of their modifiable porous structures. In this mini review, the recent advances in the use of MOFs for the adsorption of organic dyes will be summarized.